STRATEGI DINAS PARIWISATA DALAM MENGEMBANGKAN DESTINASI WISATA DI KABUPATEN PULAU MOROTAI - Iwan Muraji (Jurnal Administrasi Publik, 2023)
Strategy of the Tourism Office in Developing Tourist Destinations in Morotai Island Regency: This study aims to analyze the strategy of developing tourism destinations by the Tourism Office in Morotai Island Regency. By using a qualitative descriptive method, this study attempts to describe the strategy for developing tourist destinations in Pulau District. The study results show that the Tourism Office has implemented a tourism destination development program in infrastructure development spread over six sub-districts. These destinations are Dodola Island Tourist Area, Raja Waterfall, Sail Field, Lifao Beach, Bido Beach, Cape Sale, Tabailenge Island, Cape America, and Tanjung Garam. Data analysis and the interview process found that the tourism destination development strategy implemented by the Tourism Office needs to pay attention to the principles of tourism destination development put forward by Yoeti (2016). This can be seen from the development of tourism infrastructure not under the attractiveness, geographical location, and utilization of tourist accessibility which is the wrong target. This has an impact on the low level of tourist visits, the lack of utilization of tourist rides by tourists, and damage to tourist facilities.